2013
DOI: 10.1016/j.jconrel.2013.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Redox nanoparticle therapeutics to cancer — increase in therapeutic effect of doxorubicin, suppressing its adverse effect

Abstract: The ultimate goal of cancer chemotherapy is to achieve a cure without causing any adverse effects. We have developed a pH-sensitive redox nanoparticle (RNP(N)), which disintegrates under acidic conditions and exposes nitroxide radicals, leading to strongly scavenging reactive oxygen species (ROS). After intravenous administration of RNP(N) to tumor bearing mice, it effectively accumulated in tumors due to the leaky neovascular and immature lymphatic system and scavenged ROS, resulting in suppression of inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 32 publications
1
40
0
1
Order By: Relevance
“…We previously confirmed that orally administered RNP O strongly scavenges ROS in DSS-induced colitis mice and almost completely cures [21]. Separately, we found that intravenously administered RNP O suppresses an activation of nuclear factor kappa B (NF-kB) in cancer cells of mice with subcutaneously transplanted tumors [32]. If oral administration of RNP O works similarly in CAC mice without any adverse effects to the entire body, it will be an ideal cancer chemotherapeutics.…”
Section: Rnp O Prevents Aom/dss-induced Cac By Suppressing Inflammationmentioning
confidence: 73%
See 1 more Smart Citation
“…We previously confirmed that orally administered RNP O strongly scavenges ROS in DSS-induced colitis mice and almost completely cures [21]. Separately, we found that intravenously administered RNP O suppresses an activation of nuclear factor kappa B (NF-kB) in cancer cells of mice with subcutaneously transplanted tumors [32]. If oral administration of RNP O works similarly in CAC mice without any adverse effects to the entire body, it will be an ideal cancer chemotherapeutics.…”
Section: Rnp O Prevents Aom/dss-induced Cac By Suppressing Inflammationmentioning
confidence: 73%
“…Nitroxide radicals are covalently conjugated to the matrix and confined in the core of these nanoparticles, which shows high biocompatibility, including long-term blood circulation via intravenous administration and low toxicity [46]. In addition, RNPs have been studied as therapies for oxidative stress injuries such as cerebral and renal ischemia reperfusion injuries, hemorrhage [25,47,48] and cancer [32]. Since the pH-disintegrative character of RNP N is not suitable for CAC treatment via oral administration, we have developed an oral nanotherapeutics using RNP O with therapeutic effects against CAC model mice in this study.…”
Section: Discussionmentioning
confidence: 99%
“…After tumor‐bearing mice have been treated with intravenous injections of RNP N at a dose of 100 mg kg −1 for 4 d, the levels of ROS have been shown to be significantly decreased in tumor tissues, compared with controls (saline administration); this is in sharp contrast to the results observed with administration of LMW TEMPOL . The suppression of oxidative stress in the tumor microenvironment by RNP N has been also confirmed by the measurement of the proinflammatory cytokine, TNF‐α . To show the concept of RNP N for adjuvant effect, the effect of RNP N on the expression of NF‐κB in colon‐26 cancer cells has been evaluated in vitro.…”
Section: Treatment By Ph‐sensitive Redox Nanoparticles (Rnpn)mentioning
confidence: 98%
“…To solve these issues, we have paid attention to the covalent conjugation of the drug to the polymer backbone to prevent drug leaking. In particular, RNP N with their on–off regulation by pH are suitable design for the treatment of oxidative stress injuries after intravenous administration . RNP N disintegrates and exposes nitroxide radicals to effectively scavenge ROS in response to low pH environments such as tumors, ischemia, and inflammation regions, without leakage of drugs due to the covalent conjugation of active species to polymer backbone.…”
Section: Treatment By Ph‐sensitive Redox Nanoparticles (Rnpn)mentioning
confidence: 99%
See 1 more Smart Citation